2006
DOI: 10.1007/s11906-006-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

New drugs for hypertension: What do they offer?

Abstract: A new drug might make a positive contribution to existing therapies for hypertension by: 1) reducing blood pressure (BP) via a novel pharmacologic mechanism; 2) possessing pharmacologic or pharmacokinetic properties that make it superior to other members of its class; or 3) facilitating BP control in refractory patients. In this paper, we review four experimental agents that promise to advance therapeutics by one of these mechanisms. Aliskiren is the first in a new class of potent, orally effective renin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The primary function of renin is to eventually cause an increase in blood pressure, leading to restoration of perfusion pressure in the kidneys. Renin inhibition is indeed associated with lowering of Ang II levels and blood pressure reduction [28] . Ang II, the most active substance of RAAS, has a strong role in vascular remodeling involving vasoconstriction and promotion of development of atherosclerosis, endothelial dysfunction, hypertension and related diseases such as metabolic syndrome, through a variety of inflammation and coagulation mechanism [29,30] .…”
Section: Resultsmentioning
confidence: 99%
“…The primary function of renin is to eventually cause an increase in blood pressure, leading to restoration of perfusion pressure in the kidneys. Renin inhibition is indeed associated with lowering of Ang II levels and blood pressure reduction [28] . Ang II, the most active substance of RAAS, has a strong role in vascular remodeling involving vasoconstriction and promotion of development of atherosclerosis, endothelial dysfunction, hypertension and related diseases such as metabolic syndrome, through a variety of inflammation and coagulation mechanism [29,30] .…”
Section: Resultsmentioning
confidence: 99%
“…Renin inhibition is indeed associated with the attenuation of Ang I and Ang II levels 39 and BP reduction. 40 Aliskiren reduced BP comparably to β-blockers1, 41 diuretics, 42 ACE–Inhibitors, 43,44 and AT 1 R blockers. 40,45 The possible benefit in renin inhibition might reside in the attenuation of plasma renin activity which is increased by ACE inhibition or AT 1 R blockade.…”
Section: The Renin–angiotensin–aldosterone Systemmentioning
confidence: 98%
“…40 Aliskiren reduced BP comparably to β-blockers1, 41 diuretics, 42 ACE–Inhibitors, 43,44 and AT 1 R blockers. 40,45 The possible benefit in renin inhibition might reside in the attenuation of plasma renin activity which is increased by ACE inhibition or AT 1 R blockade. 46 On the other hand, the high renin levels after aliskiren treatment 47 might escape from renin inhibition and aliskiren may not prevent binding of renin to the (P)RR.…”
Section: The Renin–angiotensin–aldosterone Systemmentioning
confidence: 98%
“…Studies with DRI revealed that renin aggravates HF indirectly though generation of Ang I and activation of Ang I–Ang II–ATI axis or directly via renin receptors. The DRI, aliskiren has a dose-related effect on blood pressure modulation in patients [224,225]. It has been proven safe in normotensive patients from 40–640 mg with daily oral administration [226].…”
Section: Renin Activity As a Bio-target For Pharmacological Intervmentioning
confidence: 99%